Fowler's syndrome of urinary retention: A retrospective study of co‐morbidity. Issue 5 (10th April 2015) - Hoeritzauer, Ingrid; Stone, Jon; Fowler, Clare; Elneil‐Coker, Suzy; Carson, Alan; Panicker, Jalesh
Abstract : Aims: To study the frequency of pain, psychological, or functional disorders in patients with Fowler's syndrome. Methods: We carried out a retrospective chart review of patients with a diagnosis of Fowler's syndrome attending the Uro‐Neurology centre at the National Hospital for Neurology and Neurosurgery between 2009 and 2013 looking at triggering events, physical and psychological comorbidities. Results: Of 62 patients with clinical and electromyographic diagnosis of Fowler's syndrome, 31 (50%) had unexplained chronic pain syndromes, 12 (19%) of these were taking opiates. Fifteen (24%) had "functional" neurological symptoms. Abdominopelvic surgery with general anesthesia was the leading trigger (n = 21, 35%). Conclusions: We found high levels of co‐morbidity with patients having some form of pain (50%), a probable functional disorder (24%), or psychological symptoms (31%). There are several potential explanations for this association including the effect of developing an apparently unexplained distressing condition, confounding effect of opiate use or referral bias. The findings suggest a need for prospective systematic study of comorbidity for this disabling condition. Neurourol. Urodynam. 35:601–603, 2016 . © 2015 Wiley Periodicals, Inc.